Electrochemical Property and Cell Toxicity of Gold Electrode Modified by Monolayer PAMAM Encapsulated Gold Nanorods - Xueqing Zhang; Bifeng Pan; Kan Wang; Jing Ruan; Chenchen Bao; Hao Yang; Rong He; Daxiang Cui (Nano Biomedicine and Engineering, 2010)
Herein we exploit the molecular engineering capability to immobilize monolayer of polyamidoamine dendrimer on gold electrode, which exhibit enhanced charge transfer and biocompatibility. Polyamidoamine (PAMAM generation 5.0) dendrimers were used as template/stabilizers for gold nanoparticle growth, with Au@PAMAM nanoparticles serving as surface modifier to produce monolayer film. TEM, UV-vis spectroscopy, and AFM were used to characterize the formation of monolayer Au@PAMAM on gold surface. The cyclic voltammetry (CV) and Impedance measurements of Au@PAMAM modified gold electrodes demonstrate electrochemistry properties of modified electrode. Furthermore, Au@PAMAM coating can greatly increased the biocompatibility of gold electrode as determined by cell growth curves